1998
DOI: 10.1063/1.369048
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of the skutterudite Co1−xFexSb3 system

Abstract: We have examined the phase equilibrium and thermoelectric properties of Co1−xFexSb3 ternary system up to high iron context x=0.40. Traces of Sb were observed in the hot-pressed samples with x⩾0.06, and FeSb2 (Fe0.73Co0.27Sb2) compound with marcasite structure was also observed in the samples with x⩾0.25 by x-ray diffraction. The lattice parameter of Co1−xFexSb3 is slightly larger than that of the binary compound CoSb3. The Seebeck coefficient and the electrical resistivity are generally reduced by the substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
35
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 5 publications
11
35
1
Order By: Relevance
“…Yang et al 16 reported that, for Fe 0.4 Co 3.6 Sb 12 , the peak value of the lattice thermal conductivity is 7.5 W/m K, while in the case of this study, the peak value is 6.5 W/m K and 4.8 W/m K for In 0.5 Fe 0.25 Co 3.75 Sb 12 and In 0.9 Fe 0.5 Co 3.5 Sb 12 , respectively. The strongest conductivity lowering is for In 0.8 Fe 1.2 Co 2.8 Sb 12 , with a peak value of 3.1 W/m K and a room-temperature lattice conductivity of 1.6 W/m K. Katsuyama et al 19 proposed that the thermal conductivity reduction of strongly iron-doped CoSb 3 is due to phonon scattering on iron atoms and additional scattering for higher iron concentrations by precipitation of secondary iron-cobalt diantimonide phases. Yang et al 16 ascribed the strong reduction of the thermal conductivity in Fe x Co 1Àx Sb 3 to an increase of the vacancy concentration on the Co site upon iron doping, and this scenario seems to be more realistic.…”
Section: Resultsmentioning
confidence: 95%
“…Yang et al 16 reported that, for Fe 0.4 Co 3.6 Sb 12 , the peak value of the lattice thermal conductivity is 7.5 W/m K, while in the case of this study, the peak value is 6.5 W/m K and 4.8 W/m K for In 0.5 Fe 0.25 Co 3.75 Sb 12 and In 0.9 Fe 0.5 Co 3.5 Sb 12 , respectively. The strongest conductivity lowering is for In 0.8 Fe 1.2 Co 2.8 Sb 12 , with a peak value of 3.1 W/m K and a room-temperature lattice conductivity of 1.6 W/m K. Katsuyama et al 19 proposed that the thermal conductivity reduction of strongly iron-doped CoSb 3 is due to phonon scattering on iron atoms and additional scattering for higher iron concentrations by precipitation of secondary iron-cobalt diantimonide phases. Yang et al 16 ascribed the strong reduction of the thermal conductivity in Fe x Co 1Àx Sb 3 to an increase of the vacancy concentration on the Co site upon iron doping, and this scenario seems to be more realistic.…”
Section: Resultsmentioning
confidence: 95%
“…While the high mobility is thermoelectrically favorable, the high lattice thermal conductivity is not. To improve the performance of CoSb 3 toward state-of-the-art mid-temperature thermoelectric materials, extensive experimental and theoretical investigations have focused on filling the naturally formed nanosized cages with alkali metals, alkaline earth metals, or rare earth filler atoms [17,18,19,20,21], or doping at the Co and/or Sb sites [22,23], or implementing both measures simultaneously [24,25,26,27,28,29]. In the context of phonon-glass electron-crystal paradigm [3,30], the filler atoms rattle in the cage and strongly scatter the heat-carrying phonons towards a phonon-glass behavior [31], while the dopants optimize the electronic band structure towards an electron-crystal behavior [32].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Ref. 36, even a very small amount (0.1 at.%) of Fe may significantly change the temperature dependence of the Seebeck coefficient of CoSb 3 . This effect, together with the reported volatilization of Sb, 12 may explain the higher conduction-type transition temperatures.…”
Section: Methodsmentioning
confidence: 99%